Kolaborasi Pemerintah Desa, BUMDes, dan Masyarakat dalam Pengembangan Wisata Camping Outdoor Dolanan Tegal Klopo di Desa Pacet - Nabella Rizka Tianlie; Hikmah Muhaimin; Suprapto Suprapto; Santosa Santosa; Jenny Yudha Utama (Master Manajemen, 2025)
Tourism plays a crucial role in regional development, not only in terms of the economy but also in enhancing the social and cultural quality of the community. Mojokerto Regency, particularly Pacet District, has significant natural tourism potential, one of which is Camping Outdoor Dolanan (COD) Tegal Klopo. This study aims to examine the role of the Village Government in community development through the utilization of this tourism potential. The research method used is descriptive qualitative, with data collection techniques including in-depth interviews, observations, and documentation. The informants in this study include the village head, BUMDes managers, tourism site managers, and local residents. The results of the study show that the Village Government plays a strategic role in designing and implementing tourism development programs in the village. The Village Government not only plays a role in building synergy between BUMDes and the community but also actively plans promotional strategies that can attract tourists to visit COD Tegal Klopo. Additionally, the Village Government also plays a role in raising community awareness about the importance of maintaining the sustainability of the environment and local culture so that this tourism can provide long-term benefits for the village. However, this tourism development faces several challenges, such as limited facilities and a lack of trained human resources to professionally manage the tourism destination. Despite these challenges, the development of COD Tegal Klopo tourism has shown positive impacts on the local economy, with an increase in income from the tourism sector. Moreover, this tourism also helps preserve local culture and encourages active community participation in the village development process. With continued support from the Village Government, it is expected that this tourism development will continue to grow, provide greater economic benefits, and preserve local culture and the environment for a better future.